Francisco de Paula Brito : a black publisher in imperial Brazil - Godoi, Rodrigo Camargo de (Vanderbilt University Press, 2020)
"Francisco de Paula Brito: A Black Publisher in Imperial Brazil is the biography of a black merchant, printer, bookseller, and publisher who lived in Rio de Janeiro from his birth in 1809 until his death in 1861"--